Eastern promises - Lantos, Robert, 1949-; Webster, Paul.; Knight, Steven, 1959-; Cronenberg, David, 1943-; Watts, Naomi, 1968-; Mortensen, Viggo, 1958-; Cassel, Vincent, 1967-; Mueller-Stahl, Armin, 1930-; Shore, Howard; Serendipity Point Films; BBC Films; Focus Features; et al. (Universal City, Calif. : Universal Home Entertainment, 2007)
Russian-born Nikolai Luzhin is a driver for one of London's most notorious organized crime families of Eastern European origin. Semyon heads the syndicate but fortunes are tested by Semyon's volatile son and enforcer, Kirill. Nikolai's carefully maintained existence is jarred once he crosses paths at Christmastime with Anna Khitrova, a midwife at a North London hospital.
Title from container.
Widescreen.
English and French language tracks, French or Spanish subtitles, English SDH.
Originally produced as a motion picture in 2007.
Special features: 'Secrets and stories'; 'Marked for life'.
Director of photography, Peter Suschitzky ; editor, Ronald Sanders ; music, Howard Shore ; costume designer, Denise Cronenberg ; production designer, Carol Spier.
Keywords: Organized crime -- England -- London -- Drama; Midwives -- England -- London -- Drama; Russians -- England -- London -- Drama; Orphans -- England -- London -- Drama; London (England) -- Drama; Feature films; Thrillers (Motion pictures, television, etc.); Gangster films